The Starch Granule-Associated Protein EARLY STARVATION1 Is Required for the Control of Starch Degradation in Arabidopsis thaliana Leaves. Issue 6 (20th May 2016) - Feike, Doreen; Seung, David; Graf, Alexander; Bischof, Sylvain; Ellick, Tamaryn; Coiro, Mario; Soyk, Sebastian; Eicke, Simona; Mettler-Altmann, Tabea; Lu, Kuan Jen; Trick, Martin; Zeeman, Samuel C.; et al.
Abstract : Two proteins present in leaf starch granules are important for the control of starch turnover, allowing plants to match the depletion of starch reserves to the length of the night. Abstract: To uncover components of the mechanism that adjusts the rate of leaf starch degradation to the length of the night, we devised a screen for mutant Arabidopsis thaliana plants in which starch reserves are prematurely exhausted. The mutation in one such mutant, named early starvation1 ( esv1 ), eliminates a previously uncharacterized protein. Starch in mutant leaves is degraded rapidly and in a nonlinear fashion, so that reserves are exhausted 2 h prior to dawn. The ESV1 protein and a similar uncharacterized Arabidopsis protein (named Like ESV1 [LESV]) are located in the chloroplast stroma and are also bound into starch granules. The region of highest similarity between the two proteins contains a series of near-repeated motifs rich in tryptophan. Both proteins are conserved throughout starch-synthesizing organisms, from angiosperms and monocots to green algae. Analysis of transgenic plants lacking or overexpressing ESV1 or LESV, and of double mutants lacking ESV1 and another protein necessary for starch degradation, leads us to propose that these proteins function in the organization of the starch granule matrix. We argue that their misexpression affects starch degradation indirectly, by altering matrix organization and, thus, accessibility of starch polymers to starch-degrading enzymes.